2018
DOI: 10.1007/s11356-018-1338-2
|View full text |Cite
|
Sign up to set email alerts
|

Pollution characteristics of surface runoff under different restoration types in manganese tailing wasteland

Abstract: A great deal of manganese and associated heavy metals (such as Ni, Cu, Zn, Cd, Pb, etc.) was produced in manganese mining, smelting, and other processes and weathering and leaching of waste slag, which entered rainwater runoff by different means under the action of rainfall runoff. It caused heavy metal pollution in water environment to surrounding areas, and then environmental and human health risks were becoming increasingly serious. In the Xiangtan manganese mine, we studied the characteristics of nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…However, COD and BOD, which are indicators of oxygen-consuming organic matters, are relatively stable, thus the degradation of organic compounds needs more time. Moreover, studies found that COD was positive correlated with sediment levels, which means that sediment particles could work as carriers of COD contaminants from land to rivers by flush processes across the catchment scale [61,65,66]. Therefore, the human activities in the whole catchment scale played the most important role in organic pollution in water body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, COD and BOD, which are indicators of oxygen-consuming organic matters, are relatively stable, thus the degradation of organic compounds needs more time. Moreover, studies found that COD was positive correlated with sediment levels, which means that sediment particles could work as carriers of COD contaminants from land to rivers by flush processes across the catchment scale [61,65,66]. Therefore, the human activities in the whole catchment scale played the most important role in organic pollution in water body.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the T-test, discharge values had a significant difference, accordingly, three times higher in wet seasons than that in dry seasons. As organic matters from farmland were transported by sediment particles [61,65,66], the organic contaminants possibly could not be moved to receiving water and therefore were stored in farmland due to lacking enough surface runoff in dry seasons. When wet seasons occurred, increased surface runoff caused soil erosion and sediment transportation.…”
Section: Discussionmentioning
confidence: 99%
“…During the research period of December 2017 and January and February 2018 there was small amount of precipitation in winter time, that is why the ditch have smaller effect of changes of composition of water (the ditch was less influenced by the changes of water composition). The scientists [40] in his study compared the characteristics of rainfall and found out that the pollution degree of Cu and Ni was proportional to the rainfall intensity. Rainfall is showing more effect than other factors such as soil permeability or type of vegetation.…”
Section: Water Pollutionmentioning
confidence: 99%
“…In Chinese production, the production of 1 tonne of pure Mn requires nearly 8 tonnes of pyrolusite/rhodochrosite ore. As a result, large quantities of tailings are deposited. With rainfall, potentially toxic elements associated with the ore deposits may be released from the tailings, so surface runoff is a major pollution source for local rivers and groundwater [25,26].…”
Section: Sources Of Contamination From Mineral Processingmentioning
confidence: 99%